Approximation in Hilbert algebras - Saeid, A. Borumand; Havenshki, M (Scientia magna, 2008)
In this note the basic notion of rough set theory will be given. We shall introduce the notion of rough ideal and rough subalgebras of Hilbert algebra, which is a generalization of ideal and subalgebra in Hilbert algebra and we shall give some properties of the lower and upper approximation in Hilbert algebra. Finally we study fuzzy rough sets in Hilbert algebras.